2017
DOI: 10.1016/j.psychres.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The interpersonal adverse effects reported by 1008 users of antidepressants; and the incremental impact of polypharmacy

Abstract: Antidepressant drugs are being prescribed at ever increasing rates internationally, despite marginal benefit compared to placebo and a range of adverse effects. Most studies of adverse effects focus on biological phenomena. This article presents the results of an online survey of 1008 self-selected anti-depressant users in Britain, which asked about five adverse effects in the interpersonal domain. The most commonly reported among participants who took only antidepressants were: Sex Life - 43.7%, Work or Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Similarly, a UK online survey of over 1,000 AD users [26] found that 60% reported negative effects in at least one of the five interpersonal domains assessed (most commonly 'Sex life'…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a UK online survey of over 1,000 AD users [26] found that 60% reported negative effects in at least one of the five interpersonal domains assessed (most commonly 'Sex life'…”
Section: Discussionmentioning
confidence: 98%
“…The 2012 survey of over 1000 UK AD users (Read et al . ) found that 71% had never had their GP or psychiatrist raise the possibility of coming off, including 66% of those who had been on them for either 5 or 10 years. More than a third (37%) expected to be on their medication ‘for ever’.…”
Section: Relevance For Clinical Practicementioning
confidence: 99%
“…Another UK survey, of over 1000 AD users, found that 37% had been taking antidepressants for more than 5 years, and 20% for more than 10 years (Read et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…One of the reasons of this is that people with depression do not reach to their therapeutic goals [4]. Because the increase of dosage of anti-depressant agents can increase their side effects [5,6], recent efforts have focused on increasing the effectiveness of drugs [7,8].…”
Section: Introductionmentioning
confidence: 99%